Novel polymer-inorganic solid-state reaction for the synthesis of CdS nanocrystallites - Kanade, K. G.; Hawaldar, Ranjit R.; Pasricha, R.; Radhakrishnan, S.; Seth, T.; Mulik, Uttam P.; Kale, B. B.; Amalnerkar, Dinesh P. (Materials Letters, 2005)
We offer a novel polymer-inorganic solid-state reaction route for the in situ generation of nanochalcogenide semiconductor in the network of polymer which itself acts as a chalcogen source. We have exemplified feasibility of this route by reacting CdI2 with engineering thermoplastic polyphenylene sulphide (PPS). These two reactants in 1:1 and 10:1 molar ratios were simply heated at the crystalline melting temperature of PPS. The resultant products were characterized by X-ray diffractometry, Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM, with selected area electron diffraction). The prima facie observations revealed the formation of cubic nanocrystallites of US with the particle size ranging from 6 to 20 nm entrapped in modified (cyclized) PPS matrix when the reactants were taken in 10:1 molar ratio. A tentative mechanism has been suggested for such hitherto unattempted solid-state reaction. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: CdS nanocrystallites; Semiconductor; solid-state reaction; Thermoplastic polymer matrix

Effect of a focusing electric field on the formation of arc generated carbon nanotubes - Karmakar, Soumen; Nagar, Harshada; Pasricha, R.; Seth, T.; Sathe, V. G.; Bhoraskar, S. V.; Das, A. K. (Nanotechnology, 2006)
The effect of a focusing electric field on the formation of carbon nanotubes in a direct current arc-plasma is investigated. The hard deposits on the surface of the cathode are the main products, rich in multi-walled carbon nanotubes. It is seen that the focusing electric field has a distinct influence on the yield, purity and morphology of the nanotubes. The yield of the carbon nanotubes under the `focused field condition' has been found to be higher than that derived from the normal electrode configuration. It has been observed that the deposition of carbonaceous soot on the reactor wall is considerably reduced on application of the focusing electric field. Transmission electron microscopy has been used to determine the morphology of the nanotubes. In addition, Raman spectroscopy has helped in distinguishing the graphene-like structures from the disordered carbon networks and helped in analysing the morphology of the tubes. Thermal analysis gave a qualitative estimation of the relative yield of carbon nanotubes within the cathode deposits and their thermal stabilities. The crystalline nature of the samples has been confirmed by x-ray diffraction analysis. The results clearly indicate that the focusing electric field confines the positively charged carbon precursors within the cathode-anode space causing high relative yield and purity and has a distinct effect on controlling the inner diameter of the as-synthesized carbon nanotubes.